CH4 broadening and shifting coefficients in the Fermi triad of 12C16O2 in the 2 µm region. (September 2019) - Domanskaya, A.V.; Asfin, R.E.; Kyuberis, A.A.; Ebert, V.
Highlights: Broadening and shifting for the whole triad is determined. Simple empirical function for the broadening coefficients is generated. Shifting ∼ −8⋅10 –3  cm –1 /atm, with weak J -dependence. Vibrational shifting coefficient –6.2(3)10 –3  cm –1 /atm. Abstract: Novel experimental values of collisional broadening and shifting coefficients for the Fermi triad of CO2 in mixture with methane at 296.0(2) K were determined from high resolution FTIR measurements. An empirical function for the broadening coefficients is obtained: γ n ( J ′) = 0.0762(7) + 0.00320(4) · exp( − 0.039(3) ·  J ′) /cm –1 /atm, here J ′ refers to the final state, n   =  1, 2, 3 labels the Fermi components. Expanded uncertainties (2σ) for 38 out of 55 reported values are smaller than 0.5%. The absolute values of shift coefficients are about ten times smaller than the broadening, and the relative uncertainty is larger (4–5%). Graphical abstract: Image, graphical abstract